2018
DOI: 10.1002/brb3.1136
|View full text |Cite
|
Sign up to set email alerts
|

N‐back training and transfer effects revealed by behavioral responses and EEG

Abstract: IntroductionCognitive function performance decreases in older individuals compared to young adults. To curb this decline, cognitive training is applied, but it is not clear whether it improves only the trained task or also other cognitive functions. To investigate this, we considered an N‐back working memory (WM) training task and verified whether it improves both trained WM and untrained cognitive functions.MethodsAs EEG studies have noted task difficulty and age‐related changes in time‐locked EEG responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
48
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 69 publications
(137 reference statements)
14
48
1
1
Order By: Relevance
“…As in previous studies (Oelhafen et al 2013, Pergher et al 2018, we observed P3 amplitude increase in the WM training group. However, while Oelhafen et al (2013) and Pergher et al (2018) reported this effect also in a difficult WM task, we observed P3 increase only in the easier 1-back task.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As in previous studies (Oelhafen et al 2013, Pergher et al 2018, we observed P3 amplitude increase in the WM training group. However, while Oelhafen et al (2013) and Pergher et al (2018) reported this effect also in a difficult WM task, we observed P3 increase only in the easier 1-back task.…”
Section: Discussionsupporting
confidence: 90%
“…As in previous studies (Oelhafen et al 2013, Pergher et al 2018, we observed P3 amplitude increase in the WM training group. However, while Oelhafen et al (2013) and Pergher et al (2018) reported this effect also in a difficult WM task, we observed P3 increase only in the easier 1-back task. Nevertheless, we would like to note that direct comparison between our results and those of previous studies should not be made because the analyses were not similar (e.g., we conducted direct comparisons between pre and post targets, while Pergher et al 2018 analyzed training effects for target vs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1 Eight of these participants were included in N-Back training study conducted by Pergher et al (2018). They received a payment of 20 euros for participating in two experiments.…”
Section: Dataset Ii: Ku Leuvenmentioning
confidence: 99%
“…One of the commonly used techniques to probe WM is the N-Back task, a complex task that requires storage, maintenance, and manipulation of information (Chen et al, 2008 ; Jaeggi et al, 2008 ) as well as inhibitory and interference control (Oberauer, 2005 ; Kane et al, 2007 ). The N-Back task has been used in single-session behavioral (Jaeggi et al, 2010 ; Brouwer et al, 2012 ) and neurophysiological (Krause et al, 2000 ; Pesonen et al, 2007 ; Esposito et al, 2009 ; Scharinger et al, 2017 ) studies as well as in multi-session behavioral (Jaeggi et al, 2008 , 2014 ; Minear et al, 2016 ; Blacker et al, 2017 ) and neurophysiological (Chen and Mitra, 2009 ; Dong et al, 2015 ; Pergher et al, 2018 ) training studies, to name a few. Many N-Back studies focus on task difficulty at different N-levels, indicating lower ERP amplitudes for more difficult tasks (Brouwer et al, 2012 ; Herff et al, 2014 ; Scharinger et al, 2017 ; Pergher et al, 2019b ) and/or stimulus type , such as the use of spatial (for instance when the target stimulus occurs in different locations on the screen) vs. verbal (for instance when the presented stimulus is word or syllable) stimuli.…”
Section: Introductionmentioning
confidence: 99%